Consumers' willingness to pay for electricity service attributes: A discrete choice experiment in urban Indonesia - Martin Siyaranamual; Mia Amalia; Arief Anshory Yusuf; Armida S. Alisjahbana (Energy Reports, 2020)
In developing countries like Indonesia, the challenge of providing electricity services is often about how to combine commercial and development objectives optimally. In this context, good knowledge of consumers' willingness to pay (WTP) and trade-offs among electricity service attributes is of strategic value, especially when achieving development objectives involve raising electricity tariffs to consumers. This study uses a discrete choice experiment (DCE) and two estimation methods, mixed logit (MXL) and latent class logit (LCL), in order to better understand the preferences of electricity customers. Specifically, the objective of the experiment is to understand how consumers balance the trade-off among four electricity service attributes: the duration of the outage, source of electricity generated, rural electrification ratio, and tariffs. The DCE survey was conducted in Bandung (Indonesia) with 1600 questionnaires were distributed. The analysis demonstrates that consumers are willing to pay for the proposed condition, away from status-quo. For example, using MXL method to reduce the outage duration to be 2 hours/year, the WTP is ranging from IDR5,000 (USD1.18) to IDR61,500 (USD14.49) per month, depending on the size of the installed capacity. While for the increase of rural electrification ratio to 100%, it ranges from IDR17,600 (USD4.15) to IDR215,000 (USD50.64) per month. The analysis emphasizes that there is significant heterogeneity in preferences for electricity service attributes.
Keywords: 330; Willingness to pay; Choice experiments; Electricity service; Indonesia